Teaching literary translation at tertiary level: the case of scandinavian studies at Sofia University (Colloquia Comparativa Litterarum, 2025)
The paper outlines some of the challenges translation training at university level is faced with, drawing on examples from the Scandinavian Studies Programme of Sofia University St. Kliment Ohridski whose model of literary translation training has already yielded some impressive results. The boom of translations of fiction from the Nordic languages in the last decades, however, calls for streamlining literary translation curriculum to tackle both specific problems of foreign language teaching at the Programme (related mainly to acquiring several Nordic languages simultaneously) and more general ones – the deteriorating command of the Bulgarian language among students and the lack of motivation for upholding the traditionally very high standards for rendering a foreign work of fiction into Bulgarian.
Keywords: literary translation; foreign language teaching; Scandinavian studies